Golgi Associated HIF1a Serves as a Reserve in Melanoma Cells. Issue 4 (22nd September 2015) - Lakhter, Alexander J.; Lahm, Tim; Broxmeyer, Hal E.; Naidu, Samisubbu R.
ABSTRACT: Hypoxia‐inducible factor‐1alpha (HIF1a) is a key transcriptional regulator that enables cellular metabolic adaptation to low levels of oxygen. Multiple mechanisms, including lysosomal degradation, control the levels of HIF1a protein. Here we show that HIF1a protein degradation is resistant to lysosomal inhibition and that HIF1a is associated with the Golgi compartment in melanoma cells. Although pharmacological inhibitors of prolyl hydroxylation, neddylation and the proteasome inhibited degradation of HIF1a, attenuation of lysosomal activity with chloroquine did not alter the levels of HIF1a or its association with Golgi. Pharmacological disruption of Golgi resulted in nuclear accumulation of HIF1a. However, blockade of ER‐Golgi protein transport in hypoxia reduced the transcript levels of HIF1a target genes. These findings suggest a possible role for the oxygen‐dependent protein folding process from the ER‐Golgi compartment in fine‐tuning HIF1a transcriptional output. J. Cell. Biochem. 117: 853–859, 2016. © 2015 Wiley Periodicals, Inc.